Controllership in micro and small companies: A bibliometric study - da Silva, Geiza Gomes; Giacobbo, Tatiana Silva Fontoura de Barcellos (Seven Editora, 2024)
Controllership presents itself as an instrument capable of assisting senior management in planning their strategies in the formation of competitive companies for the market. Thus, the present work aims to analyze the functions of the controllership area that can be implemented in Micro and Small Companies. To this end, the content analysis method was used, to map the existing literature on the subject, with journals published between 2011 and 2021, on the SPELL platform, in which predominant characteristics in the implementation of controllership in these small organizations were identified. The main result found was that in 70.59% of the publications the authors used field research to prepare the research, and with regard to the controllership tools used in Micro and Small Companies, the management of costs and cash flow appear as the most described in the researches explored. DOI:https://doi.org/10.56238/sevened2024.018-034